Analisis Faktor-Faktor Yang Mempengaruhi Minat Penggunaan Sistem Informasi Akuntansi Pada Ukm (Studi Empiris Pada UKM di Kabupaten Karanganyar) - Rosita, Rosita (STIE Surakarta, 2013)
This study aims to determine the factors that influence SMEs in Karanganyar using accounting information system that consists of performance expectations , expectations of the business and social factors . The primary data used in this fieldwork by direct interviews using questionnaires to the respondents , the owner of Small and Medium Enterprises in Karanganyar respects to the study variables.The Analysis is using the validity and reliability testing of the questionnaire used in this study . Data was analyzed using partial regression analysis and multiple linear regression analysis . To test the hypothesis would be to use the test with the t test and F test As for the large measure explains the ability of the independent variables on the dependent variable in a regression model to be used will be measured coefficient of determination.The results obtained in this study with the âtâ test is that the expectation of performance and social factors influence positively and significantly partially on the use of AIS on SMEs in Karanganyar . For business expectations factor has no effect on the use of AIS on SMEs in Karanganyar . The test results together (synchronously) is through the F test can be concluded that the variables are jointly performance expectations , expectations of the business and social factors influence the use of AIS on SMEs in Karanganyar . By determination tests it can be concluded that the performance variable Hope , Hope Enterprises and Social factors have an influence on the use of AIS 48 % , while the rest (52%) are influenced by variables other than those used in the study